Odpowiedź:
a)
a - przyprostokątna = 1
c - przeciwprostokątna = √3
b - druga przyprostokątna = √(c² - a²) = √[(√3)² - 1²] = √(3 - 1) = √2
sinα = a/c = 1/√3 = √3/3
cosα = b/c = √2/√3 = √(2 * 3)/3 = √6/3
tgα = a/b = sinα : cosα = √3/3 : √6/3 = √3/3 * 3/√6 = √3/√6 =
= √(3 * 6)/6 = √18/6= √(9 * 2)/6 = 3√2/6 = √2/2
ctgα = 1/tgα = 2/√2 = 2√2/2 = √2
b)
a - przyprostokątna = 2√10
c - przeciwprostokątna = 11
b - druga przyprostokątna = √(c² - a²) = √[11² - (2√10)² ] =
= √(121 - 4 * 10) = √(121 - 40) = √81 = 9
sinα = a/c = 2√10/11
cosα = b/c = 9/11
tgα = a/b = 2√10/9
ctgα = b/a = 9/2√10 = 9√10/(2 * 10) = 9√10/20
c)
a - przyprostokątna = 4
b - przyprostokątna = 7
c - przeciwprostokątna = √(a² + b²) = √(4² + 7²) = √(16 + 49) = √65
sinα = a/c = 4/√65 = 4√65/65
cosα = b/c = 7/√65 = 7√65/65
tgα = a/b = 4/7
ctgα = b/a = 7/4